A Coagulation Mode on Bipolar Electrosurgery Unit Using 350 KHz Frequency and Power Selection - Prastawa Asalim Tetra Putra; Bambang Guruh Irianto; Tribowo Indrato; Lamidi Lamidi; Rizki Andriyanto; Nora Bouzeghaia (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
Losing a lot of blood during surgery using a conventional scalpel is something that is highly avoided. The purpose of this study is to replace the conventional scalpel with a tool that utilizes a high frequency whose duty cycle is regulated and then centered at one point. Researchers take advantage of the effect of heat generated by high frequencies which are centered at one point so that it can be used for the process of surgery and coagulation in body tissues so as to minimize the occurrence of a lot of blood loss. Researchers use a high frequency of 350 KHz which is set with a duty cycle of 6% on 94% off and is equipped with 3 levels of power selection and uses forceps as a medium to concentrate high frequencies at one point. The module design consists of a 350 KHz frequency generator, a pulse control circuit to adjust the duty cycle, a power control circuit as a power setting, a driver circuit to combine the frequency with the set power so that different outputs are obtained according to the settings, and an inverter circuit to increase the voltage. In this study, after measuring using an oscilloscope in the driver circuit, the average output amplitude at each low, medium, and high setting was 27.25 Vpp, 28 Vpp, and 28.625 Vpp. The results showed that the bipolar electrosurgery unit (coagulation) module as a whole can replace conventional scalpels so that it can minimize the occurrence of a lot of blood loss during surgery. However, the frequency generator and power selection need to be improved.